2018
DOI: 10.1007/978-3-030-00828-4_34
|View full text |Cite
|
Sign up to set email alerts
|

A Replay Speech Detection Algorithm Based on Sub-band Analysis

Abstract: With the development of speech technology, various spoofed speech has brought a serious challenge to the automatic speaker verification system. The object of this paper is replay attack detection which is the most accessible and can be highly effective. This paper investigates discrimination between the replay speech and genuine speech in each sub-band. For sub-bands with discrimination information, we propose a new filter design approach. Finally, experiments are conducted on the ASV spoof 2017 data set using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…The results here agree with the finding in the study [41], which found that 0-0.5 kHz and 7-8 kHz sub-bands were more discriminative than other frequency bands. Another study [42], which used the RP for analysis, reported that 0-1 and 4-5 kHz were more informative and discriminative.…”
Section: E) Frequency Importance Analysissupporting
confidence: 93%
“…The results here agree with the finding in the study [41], which found that 0-0.5 kHz and 7-8 kHz sub-bands were more discriminative than other frequency bands. Another study [42], which used the RP for analysis, reported that 0-1 and 4-5 kHz were more informative and discriminative.…”
Section: E) Frequency Importance Analysissupporting
confidence: 93%
“…In the context of spoofing detection, the most relevant studies include [19,20,21,22,23,24]. The authors of [19] investigated different subbands to find the most informative bands useful for spoofing detection tasks.…”
Section: Relation To Prior Workmentioning
confidence: 99%
“…In our previous research on ASVspoof 2017 dataset, we performed a detailed analysis of the differences between genuine speech and the replay speech on the frequency sub-bands. Our research showed that the discriminative information of genuine speech and replay speech is mainly distributed in two sub-bands, i.e., 0-1 kHz and 7-8 kHz [12] [13]. one plausible explanation for this observation can be as follows.…”
Section: Introductionmentioning
confidence: 66%